Macrophage migration inhibitory factor induces epithelial to mesenchymal transition, enhances tumor aggressiveness and predicts clinical outcome in resected pancreatic ductal adenocarcinoma. Issue 4 (14th September 2012) - Funamizu, Naotake; Hu, Chaoxin; Lacy, Curtis; Schetter, Aaron; Zhang, Geng; He, Peijun; Gaedcke, Jochen; Ghadimi, Michael B.; Ried, Thomas; Yfantis, Harris G.; Lee, Dong H.; Subleski, Jeffrey; et al.
Abstract MIF is a proinflammatory cytokine and is implicated in cancer. A higher MIF level is found in many human cancer and cancer‐prone inflammatory diseases, including chronic pancreatitis and pancreatic cancer. We tested the hypothesis that MIF contributes to pancreatic cancer aggressiveness and predicts disease outcome in resected cases. Consistent with our hypothesis we found that an elevated MIF mRNA expression in tumors was significantly associated with poor outcome in resected cases. Multivariate Cox‐regression analysis further showed that MIF is independently associated with patients' survival (HR = 2.26, 95% CI = 1.17–4.37, p = 0.015). Mechanistic analyses revealed that MIF overexpression decreased E‐cadherin and increased vimentin mRNA and protein levels in pancreatic cancer cell lines, consistent with the features of epithelial‐to‐mesenchymal transition (EMT). Furthermore, MIF‐overexpression significantly increased ZEB1/2 and decreased miR‐200b expression, while shRNA‐mediated inhibition of MIF increased E‐cadherin and miR‐200b expression, and reduced the expression of ZEB1/2 in Panc1 cells. Re‐expression of miR‐200b in MIF overexpressing cells restored the epithelial characteristics, as indicated by an increase in E‐cadherin and decrease in ZEB1/2 and vimentin expression. A reduced sensitivity to the chemotherapeutic drug, gemcitabine, occurred in MIF‐overexpressing cells. Indicative of an increased malignant potential, MIF over‐expressing cells showed significant increase in their invasion ability in vitro, and tumor growth and metastasis in an orthotopic xenograft mouse model. These results support a role of MIF in disease aggressiveness, indicating its potential usefulness as a candidate target for designing improved treatment in pancreatic cancer.